CHALLENGES IN COORDINATING A SECURITY ARRANGEMENTIN MALACCA STRAIT - MUHAMMAD SAERI (Indonesian Journal of International Relations, 2019)
ABSTRACT Melaka Strait is a border area of some South East Asia countries, especially three countires which get in touch directly with this area that are Indonesia, Malaysia, and Singapore. Melaka Strait as a suit region for the three countries has strategik position in many aspects, especially ideology, security, and economiy. According to idiological aspect Melaka Strait is a part of teritory of the three countries which dealing with their sovereignty. Based on this principal, Indonesia and Malaysia considered that Malaka Strait is integrate to the sovereignty of these coutries, so that security arrangement of the strait should submit to the regulation authority of the both coutries. In difference side, Singapore considers that security management of Melaka Strait is not dealing with states sovereignty, and put Malaka Straits into international security management will never disturb the sovereignty of the coutries surrounding the strait. Singapore believe that international cooperation of Malaka Strait management with others maritime power is needed. Considered to security aspect, Melaka Straits is one of regions with high risk and high cases robbery in the world. Until this time Indonesia , Malaysia, and Singapore are not able perfectly yet to stop the robbery strike problems in Melaka Straits. The development of political scurity today also put Melaka Straits into open position to get negative impact of South Cina Sea konflict dealing with Spratly Islands between Cina and several ASEAN countries. Malaka Straits also came open to be a target of terrorisme attact, althou real indication to this case is not found yet. Melaka Straits considered to economy aspect, is a crowded shipping line area which passed through by international voyages. As an international trading line this straits conduct significant role as a supporting factor of world economy development. The strategik position of Malaka straits give a very big impact to economy development of countries surrounding this area. According to this important role, so that security of Melaka Straits should to become reality, and this matter is challenge to Indonesia, Malaysia, and Singapore.